2021
DOI: 10.1177/21925682211017478
|View full text |Cite
|
Sign up to set email alerts
|

Cervicothoracic Versus Proximal Thoracic Lower Instrumented Vertebra Have Comparable Radiographic and Clinical Outcomes in Adult Cervical Deformity

Abstract: Study Design: Comparative cohort study. Objective: Factors that influence the lower instrumented vertebra (LIV) selection in adult cervical deformity (ACD) are less reported, and outcomes in the cervicothoracic junction (CTJ) and proximal thoracic (PT) spine are unclear. Methods: A prospective ACD database was analyzed using the following inclusion criteria: LIV between C7 and T5, upper instrumented vertebra at C2, and at least a 1-year follow-up. Patients were divided into CTJ (LIV C7-T2) and PT groups (LIV T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…LIV selection is considered a key component in preventing DJK, aiming to avoid the curve’s apex [ 26 ]. However, the relationship between DJK and the LIV after cervical realignment surgery has received limited attention in the literature [ 22 , 23 , 27 ].…”
Section: Fusion-level Selection In Csdmentioning
confidence: 99%
See 2 more Smart Citations
“…LIV selection is considered a key component in preventing DJK, aiming to avoid the curve’s apex [ 26 ]. However, the relationship between DJK and the LIV after cervical realignment surgery has received limited attention in the literature [ 22 , 23 , 27 ].…”
Section: Fusion-level Selection In Csdmentioning
confidence: 99%
“…A study by Kim et al [ 27 ] compared CSD patients with LIV at the CTJ versus the proximal thoracic (PT) spine. The results revealed that patients with fusion to the PT spine demonstrated larger cSVA malalignment, greater T1S–CL mismatch, and a higher likelihood of requiring a pedicle subtraction osteotomy for correction.…”
Section: Fusion-level Selection In Csdmentioning
confidence: 99%
See 1 more Smart Citation